Pengaruh Keadilan terhadap Kepuasan dan Kepatuhan Wajib Pajak - Albari, Albari (Unisia, 2012)
In general, tax payment has been perceived merely as a citizen’s obligation which has to be performed, paying less attention to the interests of Tax Payers. Therefore, this study proposes to reveal possibilities of Tax Payers’ compliance because of just services given by Tax Office and of Tax Payers’ satisfaction upon the justice itself. In this research, concept of justice is classified into distributive, procedural and interactional justices. This research involves 166 respondents, gained through convenience sampling from Tax Payers in KPP II. Using path analysis, this research results in the fact that justice affects, directly or indirectly, the compliance through intervening variable of satisfaction. Whilst based on regression analysis, it has been shown that distributive justice and the satisfaction of Tax Payers upon procedural justice positively affect the Tax Payers’ compliance. Keywords: justice, satisfaction, compliance.